1992
DOI: 10.1111/j.1445-2197.1992.tb07559.x
|View full text |Cite
|
Sign up to set email alerts
|

Single Dose Ceftriaxone as Prophylaxis for Sepsis in Colorectal Surgery

Abstract: During the period May 1986 to July 1989, a prospective, double blind, randomized trial of antibiotic prophylaxis in colorectal surgery was undertaken at the Royal Brisbane Hospital. Three hundred and thirty patients were considered eligible for the trial. Three regimens were compared: a combination of 2 g ceftriaxone and 1 g metronidazole; a single dose of 2 g ceftriaxone; or 1 g cefazolin and 1 g metronidazole, as antibacterial prophylaxis in colorectal surgery. Fifty patients were excluded from analysis. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 6 publications
1
40
0
1
Order By: Relevance
“…Although in one study, the authors concluded that it is not always necessary to give metronidazole in addition to ceftriaxone for perioperative prophylaxis [7], many authors have recommended this combination as advantageous [8,9]. In the present study, metronidazole was combined with ceftriaxone in approximately 65% of cases, compared to 80% with other cephalosporins and only approximately 50% with penicillin.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Although in one study, the authors concluded that it is not always necessary to give metronidazole in addition to ceftriaxone for perioperative prophylaxis [7], many authors have recommended this combination as advantageous [8,9]. In the present study, metronidazole was combined with ceftriaxone in approximately 65% of cases, compared to 80% with other cephalosporins and only approximately 50% with penicillin.…”
Section: Discussionmentioning
confidence: 77%
“…In a prospective randomized double-blind study of perioperative prophylaxis with ceftriaxone 2 g B metronidazole versus cefazolin 1 g + metronidazole in colorectal surgery [7], postoperative airway and urinary tract infections were more frequent with cefazolin (p ! 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…agents, most commonly metronidazole. 452,[459][460][461][462] However, in all but one of these studies, a combination of a secondor third-generation cephalosporin plus metronidazole was no more effective than the cephalosporin alone. The use of third-or fourthgeneration cephalosporins for routine antimicrobial prophylaxis is not recommended as use may lead to development of resistant organisms.…”
Section: Efficacymentioning
confidence: 99%
“…456,460,461 In some studies, second-or thirdgeneration cephalosporins were combined with other i.v. agents, most commonly metronidazole.…”
Section: Efficacymentioning
confidence: 99%
“…Eine Reihe von antibiotikaorientierten Studien scheinen dagegen aber den Wert einer Prophylaxe zu bestätigen [29,35,43]. Das Design der genannten Studien weist aber in der Regel Schwächen auf, da diese nicht placebokontrolliert waren oder Daten aus der Dickdarmchirurgie über-nommen wurden.…”
Section: Offene Prostatektomienunclassified